Exploring the status of community capacity building towards urban poverty alleviation in Kuala Lumpur, Malaysia - Dass, Mahaganapathy; Gill, Sarjit S.; Kunasekaran, Puvaneswaran (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This paper presents the level of community capacity building attained by the urban poor minority group of MyKasih program participants towards urban poverty alleviation in Kuala Lumpur, Malaysia. MyKasih is one of the Non-governmental Organization focused to combat urban poverty issues in the country. This study was conducted at Kuala Lumpur urban squatters’ concentrated destination in Kuala Lumpur, Malaysia. Qualitative approach was used where in-depth interview was used as the data collection method. The results show that the community does not have full capacity and they are still dependent on outsiders’ assistance. It is hoped that the findings of this study will contribute to existing body of knowledge within urban poverty and community development disciplines.